2018
DOI: 10.2340/16501977-2304
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of performance-based outcome measures for mobility, balance, muscle strength and manual dexterity in adults with myotonic dystrophy type 1

Abstract: The performance-based outcome measures captured changes over the 9-year period and responsiveness was promising. Knowledge of measurement errors is needed to interpret the meaning of these longitudinal changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…A significant increase in hip flexor strength assessed by stationary dynamometry was found in this study as well as in a previous DM1 study. 8 However, this is considered a spurious type II error finding because of no change in physical activity level in this study and the loss of hip flexor strength recorded by HHD in the present-and a previous DM1 study. 14 This study demonstrated loss of strength in knee and hip flexors and ankle plantar flexors assessed by HHD.…”
Section: Muscle Strength Measurementsmentioning
confidence: 51%
See 4 more Smart Citations
“…A significant increase in hip flexor strength assessed by stationary dynamometry was found in this study as well as in a previous DM1 study. 8 However, this is considered a spurious type II error finding because of no change in physical activity level in this study and the loss of hip flexor strength recorded by HHD in the present-and a previous DM1 study. 14 This study demonstrated loss of strength in knee and hip flexors and ankle plantar flexors assessed by HHD.…”
Section: Muscle Strength Measurementsmentioning
confidence: 51%
“…The objective measurements were generally poorly reflected by the subjective scoring of changes in muscle strength, balance, and functional mobility using the GRS after 1 year. This relationship was better matched when the observation period was 9 years, 8 where larger changes occur that can be more easily perceived. However, overall the true agreement between the objective measurements and subjective assessments in this study is somewhere Step test: missing values (n = 1) because patient did not finish the test due to knee pain.…”
Section: Outcome Measures Against Grsmentioning
confidence: 89%
See 3 more Smart Citations